Racing for What? Anticipation and Acceleration in the Work and Career Practices of Academic Life Science Postdocs - Ruth Müller (Forum: Qualitative Social Research, 2014)
In the wake of contemporary new public management, the temporalities of academic work have undergone significant transformations. One key feature of these changes is a perceived acceleration of working pace. While this phenomenon is widely acknowledged in scholarship about the transforming universities, to date there are only few studies investigating its empirical details. Building on qualitative interviews with 38 postdoctoral life scientists in Austria, this article investigates how these researchers experience the temporalities of their work and career practices. Postdocs are particularly susceptible to the changing demands of academic work life, as they mostly inhabit fragile institutional positions while they aspire to establish themselves in academia. The experience of being in a highly competitive race that requires a continuously accelerating working pace as well as a strong focus on individual achievement is central to their narratives about working for a career in academia. Drawing on recent scholarship on anticipation (ADAMS, MURPHY & CLARKE, 2009), acceleration (ROSA, 2003) and the entrepreneurial self (BRÖCKLING, 2007), I develop the concepts of anticipatory acceleration and latent individualization to analytically capture postdocs' experiences of temporalities in the context of their work and career practices. In conclusion I discuss the possible impacts of these particular temporal orientations for the contents and formats of academic knowledge production and ask in how far concepts and movements such as "slow science" help to address effects and problems of these specific forms of acceleration and anticipation.